Memorandum of Understanding between the BRAC University and International Centre for Diarrhoeal Disease Research Bangladesh (2007) - BRAC University; International Centre for Diarrhoeal Disease Research Bangladesh (BRAC University and International Centre for Diarrhoeal Disease Research Bangladesh, 2013)
1. Parties - (a) BRAC Universities and (b) International Centre for Diarrhoeal Disease Research Bangladesh. 2. Background. 3. Roles and Responsibilities of BRAC and ICDDRB.